2019
DOI: 10.1002/celc.201801780
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Ultrathin PEDOT on Carbon Nanotubes and Shear Thinning Xanthan Gum‐H2SO4 Gel Electrolyte for Supercapacitors

Abstract: Resistance of the electrode material play a vital role for applications in supercapacitors, where lowering the resistance leads to improved performance. Poly(3,4-ethylene dioxythiophene) (PEDOT) possesses high theoretical conductivity; however, the high density of grain boundaries, low accessible surface area, and low rate capability have been pervasive issues affecting the PEDOT-based supercapacitors. To this end, a hydrothermal method is proposed in this work where oxygen functional groups incorporated on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…In addition, this configuration may offer a strong synergistic effect, which improves the capacitive properties regarding the specific capacitance values and the cycling stability. Various conducting polymer/carbon material composites have been studied such as PPy/CNT, 14,[21][22][23] PANI/CNT, [24][25][26] poly(3,4-ethylenedioxythiophene) (PEDOT)/CNT, [27][28][29] PANI/Gr, 30,31 and PPy/Gr. [32][33][34] Cherusseri et al showed that oxidized-carbon nanotubes/PPy nanocomposite exhibits a specific capacitance of about 80 F•g -1 at a current density of 7 mA•cm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, this configuration may offer a strong synergistic effect, which improves the capacitive properties regarding the specific capacitance values and the cycling stability. Various conducting polymer/carbon material composites have been studied such as PPy/CNT, 14,[21][22][23] PANI/CNT, [24][25][26] poly(3,4-ethylenedioxythiophene) (PEDOT)/CNT, [27][28][29] PANI/Gr, 30,31 and PPy/Gr. [32][33][34] Cherusseri et al showed that oxidized-carbon nanotubes/PPy nanocomposite exhibits a specific capacitance of about 80 F•g -1 at a current density of 7 mA•cm -2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, CNTs belong to the mechanism of double electric energy storage, which only relies on the electronic adsorption to provide the capacitance performance, and exhibited poor capacitor performance as electrodes, which may seriously limit their applications. In this regard, CNTs could be dispersed in polymer matrix served as an additional path for charge transfer as electrode materials [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the voltage range of capacitors in different electrolyte environments is shown in Figure 3h, in which we can observe that most of the voltage ceilings in acidic, [6,13,[25][26][27] alkaline [3,4,28,29] and even organic electrolytes [30][31][32] were in the range from 1.0 to 1.5 V, and the voltage windows of many other aqueous ion capacitors such as aqueous lithium ion and sodium ion capacitor in recent research, reached 2.0 V. [33][34][35][36] In this work, the upper limits of voltage ranges have been enhanced to 2.2 and 2.5 V in "WiS" and Et 4 NBF 4 /PC electrolyte, respectively. Besides, both Zn-BP-WiS and Zn-BP-PC exhibited excellent cycling stability (more than 5000 and 9500 cycles) and outstanding Faraday capacitances (304 and 363.9 F g −1 at 0.5 A g −1 ).…”
Section: Resultsmentioning
confidence: 99%